2002
DOI: 10.1074/jbc.m201394200
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Activation of Protein-tyrosine Phosphatase α and Regulation of Its Src-mediated Transforming Activity by Its Sites of Protein Kinase C Phosphorylation

Abstract: During mitosis, the catalytic activity of protein-tyrosine phosphatase (PTP) ␣ is enhanced, and its inhibitory binding to Grb2, which specifically blocks Src dephosphorylation, is decreased. These effects act synergistically to activate Src in mitosis. We show here that these effects are abrogated by mutation of Ser 180 Protein-tyrosine phosphatase (PTP)1 ␣ is an ϳ130-kDa transmembrane PTP (1, 2) that activates the cytoplasmic membrane-bound Src protein-tyrosine kinase by dephosphorylating Src Tyr(P) 527 (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 41 publications
4
63
1
Order By: Relevance
“…The same results were obtained by the use of purified PKC from rat brain and a GST fusion protein of PTP␣ in an in vitro kinase assay. In addition, it has been shown that changing these serine residues to alanine diminished the ability of PTP␣ to activate Src after mitotic stimulation in vivo (27). Therefore, these phosphorylation sites must be, at least in part, necessary for the regulation and activation of PTP␣.…”
Section: Discussionmentioning
confidence: 99%
“…The same results were obtained by the use of purified PKC from rat brain and a GST fusion protein of PTP␣ in an in vitro kinase assay. In addition, it has been shown that changing these serine residues to alanine diminished the ability of PTP␣ to activate Src after mitotic stimulation in vivo (27). Therefore, these phosphorylation sites must be, at least in part, necessary for the regulation and activation of PTP␣.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, this kinase could in turn activate the PTP1b in a signaling complex. There are many examples where a protein tyrosine phosphatase regulates kinase function [37][38][39][40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…For example Src family PTKs (SFKs) are required for G 2 progression, mitotic entry, spindle orientation and cytokinesis, [23][24][25][26][27][28] JAK PTKs may be required for cytokinesis 29 and PTPs such as PTP-BL 30 and PTP-PEST 31,32 may regulate cytokinesis. Also, we recently reported that the tyrosine phosphatase TCPTP negatively regulates SFKs at the G 2 /M transition, 33 whereas others have shown that the tyrosine phosphatase PTPα activates SFKs in mitosis, 34,35 thus highlighting the requirement for integrated PTP/PTK responses long after the impact of mitogens in G 1 . Furthermore, tyrosine phosphorylation of the p53 paralog p73 and its transcriptional co-activator Yap1 by the c-Abl PTK is involved in the apoptotic response to DNA damage, [36][37][38][39] whereas the PTP Shp2 is thought to positively contribute to the G 2 /M DNA damage response, at least in part through the regulation of c-Abl.…”
Section: Tyrosine Phosphorylation and The Cell Cyclementioning
confidence: 99%